2014
DOI: 10.3109/02688697.2014.887657
|View full text |Cite
|
Sign up to set email alerts
|

Yield and complications of frame-based and frameless stereotactic brain biopsy – The value of intra-operative histological analysis

Abstract: We advocate intra-operative histopathological analysis to decrease negative biopsy rates and advise increased caution when undertaking biopsies of deep lesions or suspected lymphoma cases due to the potentially increased risk of haemorrhage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 35 publications
2
50
0
Order By: Relevance
“…Smith et al (33) reported that there were no significant differences regarding the incidence of complications between frame-based and frameless biopsy. Platelet counts below 150,000/mm 3 (11), liver cirrhosis (6), deep location and lymphoma (25) were found to be increased risk factors for hemorrhage. Owen et al (28) reported that all cases bleeding through the biopsy needle were able to be stopped by continuing irrigation.…”
Section: Diagnostic Yield and Accuracymentioning
confidence: 97%
See 1 more Smart Citation
“…Smith et al (33) reported that there were no significant differences regarding the incidence of complications between frame-based and frameless biopsy. Platelet counts below 150,000/mm 3 (11), liver cirrhosis (6), deep location and lymphoma (25) were found to be increased risk factors for hemorrhage. Owen et al (28) reported that all cases bleeding through the biopsy needle were able to be stopped by continuing irrigation.…”
Section: Diagnostic Yield and Accuracymentioning
confidence: 97%
“…Many predictive factors for non-diagnostic biopsy have been described, including younger age (11,23), longer operating time (10), insufficient material and sampling error (4), lesions locating at right side (10), midline and cerebellum (9,25), smaller and deeply located lesions and posterior fossa lesions (3). A misdiagnosis is an incorrect diagnosis and occurs most often with mis-staged glial tumors during stereotactic brain biopsies (36).…”
Section: Non-diagnosis and Misdiagnosismentioning
confidence: 99%
“…2,3,5,6,8,10,12 Complication rates from these cases series have ranged from 6-12%, 2,4,7 with permanent morbidity 3,5,8,9,12 and mortality 2,3,5-9,12 ranging from 3.1-6.4% and 0-1.7%, respectively. Data from a larger meta-analysis similarly found a major morbidity rate of 3.5% and a mortality rate of only 0.7%, with a positive histological diagnosis in 91% of all cases.…”
Section: Introductionmentioning
confidence: 98%
“…3,5,8,11 Interestingly, most studies reported that only half (3.4-5.2%) of detected hemorrhages were symptomatic. 2,3,[5][6][7][8][9] M A N U S C R I P T…”
Section: Introductionmentioning
confidence: 99%
“…Marginal tissue may be non-diagnostic because it shows only inflammation or gliosis; more central tissue could show necrosis.Insufficient volume of tissue may be acquired to make the correct diagnosis [22] . While a diagnostic accuracy of 95% has been reported for neoplastic processes with stereotactic biopsy [23,24,25] , multiple biopsy sites may be required to achieve this goal [25,26] , particularly for deep-seated or cerebellar lesions. Biopsy results can direct subsequent clinical care in these patients, but the absolutely correct diagnosis on stereotactic biopsy compared to resected samples in the same population may only be 63% [5] .…”
mentioning
confidence: 99%